Design Of Hybrid Cryptography With Vigenere Cipher And RSA Algorithm On IOT Data Security - Safira, Maria Okta; Ari Mogi, I Komang (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 8 No 4 (2020): JELIKU Volume 8 No 4, Mei 2020DO - 10.24843/JLK.2020.v08.i04.p14, 2020)
In this paper two methods are used, namely the vigenere cipher method and the RSA method. The vigenere cipher method is an example of a symmetric algorithm, while RSA is an example of an asymmetric algorithm. The combination of these two methods is called hybrid cryptography which has the advantage in terms of speed during the encryption process. Each process, which is encryption and decryption, is carried out twice, so that security can be ensured. In the process of forming the key used the RSA method. In the encryption process using public keys that have been generated before when the key is formed. This public key is used in sending data to the recipient of a secret message where this key is used for the data encryption process. The Secret key is kept and will be used during the decryption process. There is a system architecture that describes how clients and servers communicate with each other over the internet using the TCP protocol where the client here is an IoT device and the server is a server.